Study of Density Distribution in Entrained Plasma - Baghdad Science Journal (مجلة بغداد للعلوم)
A theoretical investigation is carried out to study the effect of a pencil electron beam propagating inside the plasma region determining the hydrodynamic densities distribution with the aid of numerical analysis finite deference method (FDM).The plasma is generated and trapped by annular electron beams of fixed electron density 1x1014 m-3. The result of the study shows that the hydrodynamic density behaves as the increase in pencil electron beam. The hydrodynamic density ratio goes to more than double as the increase in pencil electron beam density to 1x1018 m-3.